Analysis of Reverse Logistics Implementation in Improving Operational Efficiency - Arzety, Zahra; Pulansari, Farida (Jurnal Sistem Cerdas, 2025)
In the era of globalization and increasingly fierce competition, some industrial companies are required to focus not only on product and distribution efficiency but also on post-consumer product management. Supply chain issues need to be considered because they are related to the productivity of the company, if the supply chain management of a company runs well, the company's goals will be achieved, and vice versa. In addition to helping implement the principle of reducing, reusing, and recycling, reverse logistics also acts as feedback from customers on the product (finished or unfinished), including the sustainability aspect of the product. The frequent return of kWh (kilowatt-hour) meters in households thatoccur returns/defects and are returned from the reporting of consumers or customers that still exist and also the handling of companies that have not met the standards and strategies for the future. The results of the analysis of the maturity level of the implementation of reverse logistics in these three companies can be categorized at level 3 (Developed Level) with the results of measurements using MSI (Method of Successive Interval) successively are 2.549; 2.292; 2.459; 2.932; 2.677. With the calculation of scores on IFE and EFE in the IE matrix, it is in quadrant II (medium-high).